2016
DOI: 10.5194/bg-13-3427-2016
|View full text |Cite
|
Sign up to set email alerts
|

Variability in <sup>14</sup>C contents of soil organic matter at the plot and regional scale across climatic and geologic gradients

Abstract: Abstract. Soil organic matter (SOM) forms the largest terrestrial pool of carbon outside of sedimentary rocks. Radiocarbon is a powerful tool for assessing soil organic matter dynamics. However, due to the nature of the measurement, extensive 14C studies of soil systems remain relatively rare. In particular, information on the extent of spatial and temporal variability in 14C contents of soils is limited, yet this information is crucial for establishing the range of baseline properties and for detecting potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
(60 reference statements)
1
26
0
Order By: Relevance
“…Radiocarbon analyses on soils have a great potential for the study of carbon turnover, yet time lags between assimilation and incorporation in soils as well as lateral and vertical spatial heterogeneity can challenge interpretations (Trumbore 2009; Van der Voort et al 2016). We therefore chose not to attempt source apportionment on the chernozem soil due to the absence of sufficient age constraints on charred soil organic matter (Carcaillet 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Radiocarbon analyses on soils have a great potential for the study of carbon turnover, yet time lags between assimilation and incorporation in soils as well as lateral and vertical spatial heterogeneity can challenge interpretations (Trumbore 2009; Van der Voort et al 2016). We therefore chose not to attempt source apportionment on the chernozem soil due to the absence of sufficient age constraints on charred soil organic matter (Carcaillet 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The present investigation employs 14 C primarily as a biological source indicator, shedding new light on the origin of individual n-alkanes and n-alkanoic acids in Lake Pavin. Lake ecosystems are diverse, and the same biomarker approach may not work in different settings, as evidenced by previous lacustrine CSRA investigations (Douglas et al, 2014;Uchikawa et al, 2008). Here we add detailed constraints on carbon cycling in a meromictic lake to better understand the dynamics pertinent to an ultraproductive, stratified lacustrine ecosystem.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies based on CSRA have so far revealed complicated, site-specific patterns of OC cycling and transport across terrestrial and lacustrine reservoirs. Uchikawa et al (2008) found reasonably good age agreement between long-chain (C 27 -C 33 , odd-numbered chains) n-alkanes and higher plant macrofossils in a sediment core from a Hawaiian karstic pond, suggesting that these compounds could be suitable for independent age scale generation. In contrast, Douglas et al (2014) determined centennial-to millennial-scale age offsets between long-chain (C 26 -C 32 , even-numbered chains) n-alkanoic acids and terrigenous macrofossils preserved in a sediment core from Lake Chichancanab in Mexico, consistent with a source of aged OC from soil erosion.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Terrestrial carbon turnover time remains one of the largest uncertainties in climate model predictions (Carvalhais et al, 2014;He et al, 2016). At present, there is no consensus on the net effect that climate and land use change will have on SOM stocks (Crowther et al, 2016;Gosheva et al, 2017;Melillo et al, 2002;Schimel et al, 2001;Trumbore and Czimczik, 2008). Deep soil carbon is of particular interest because of its large stocks (Jobbagy and Jackson, 2000;Balesdent et al, 2018;Rumpel and Kögel-Knabner, 2011) and perceived stability.…”
Section: Introductionmentioning
confidence: 99%